Dynamic Causality Relationship between Bitcoin and Global Islamic Equity Markets: A Pre- and Post-COVID-19 VECM Analysis - Dhani, Rifqi Rama; Oktaviana, Helmalia; Sulistiyah, Sulistiyah; Subagiyo, Rokhmat; Aswad, Muhammad (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study explores the dynamic interactions between Bitcoin (BTC), the Dow Jones Islamic Market Index (DJIMI), and the FTSE SGX Shariah 100 Index (FTSGS100) from 2015 to 2025, employing the Vector Error Correction Model (VECM) to analyze both short- and long-term relationships. The Johansen cointegration test indicates a long-term equilibrium among the three variables, with DJIMI showing a stronger connection to Bitcoin compared to FTSGS100. In the short run, Bitcoin exhibits a strong response to its own shocks, whereas the Sharia indices are more stable and less responsive to short-term fluctuations in Bitcoin’s volatility. The findings underscore the weak integration between global Sharia equity markets and digital assets, positioning Bitcoin as a speculative asset largely independent of Sharia-compliant markets. These results suggest the importance of enhanced risk management and portfolio diversification strategies for investors navigating the rapidly changing financial landscape. Additionally, this research enhances our understanding of the interactions between cryptocurrency markets and traditional financial markets, particularly Sharia-compliant indices, during times of global financial uncertainty.